A Novel Post-FFT OFDM Receiver Beamforming in the Presence of Downconverter Impairments - Laco, Juan Matías (2013)
In this paper, two non-desired effects, interference and in-phase/quadrature (I/Q) imbalance, are jointly compensated at the receiver side of an Orthogonal Frequency Division Multiplexing (OFDM) system. Taking information of the known pilots transmitted within the symbol, a Post-FFT receiver beamforming based on an NLMS algorithm is proposed to adapt the beamforming weights to reject interference signals and to compensate I/Q imbalance. Our simulation results show that the proposed Post-FFT receiver beamforming compensates I/Q imbalance without degrading the interference rejection of the array.